Immunogenicity and Antibody Persistence of the Inactivated Quadrivalent Influenza Vaccine in Pediatric Patients Post-Chemotherapy or Allogeneic Hematopoietic Stem Cell Transplantation Versus Healthy Controls - Mi Yeon Hur; Kyu Ri Kang; Ye Ji Kim; Yoon Kyung Cho; Jae Wook Lee; Nack-Gyun Chung; Bin Cho; Dae Chul Jeong; Jin Han Kang; Hyun Mi Kang (Vaccines)
Pediatric patients who have undergone hematopoietic stem cell transplantation (HSCT) or chemotherapy are at increased risk for severe influenza complications, necessitating annual vaccination. This study evaluated the immunogenicity and antibody persistence of the 2021–2022 seasonal quadrivalent influenza vaccine in pediatric patients post-HSCT or chemotherapy, compared to healthy controls. A prospective cohort study included 80 pediatric participants divided into three groups: chemotherapy (n = 33), HSCT (n = 27), and healthy controls (n = 20). All participants were vaccinated with the 2021–2022 GC FLU Quadrivalent vaccine. Hemagglutination inhibition (HI) assays measured seroprotection rates (SPR), geometric mean titers (GMT), and seroconversion rates (SCR) for the four vaccine antigens (A/H1N1, A/H3N2, B/Victoria, B/Yamagata) at one, three, and six months post-vaccination. At one month post-vaccination, all groups met the 70% SPR threshold for A/H1N1 and A/H3N2, but not for B/Victoria. For B/Yamagata, the SPR was low in the chemotherapy and HSCT groups (18.18% and 33.33%, respectively), compared to 80.00% in controls (p < 0.0001 and p = 0.0015). While A/H1N1 and A/H3N2 GMTs were protective in all groups, only controls achieved protective levels for B/Yamagata. Over time, the control group maintained >70% SPR for A/H1N1 up to six months, but the chemotherapy and HSCT groups declined by three and six months, respectively. For A/H3N2, the SPR in controls dropped below 70% at three months, while it remained above 70% in the chemotherapy and HSCT groups until three months. None of the groups achieved protective GMTs for B strains at three or six months. Pediatric patients post-HSCT or chemotherapy demonstrated a comparable immune response to healthy controls for A/H1N1 and A/H3N2, but the rapid decline in A/H1N1 antibody levels suggests the need for ongoing monitoring and adjusted vaccination schedules. The poor response to B antigens, particularly B/Yamagata, underscores the need for improved vaccination strategies in these vulnerable populations.